2000
DOI: 10.1097/00000539-200003000-00040
|View full text |Cite
|
Sign up to set email alerts
|

Patch-Clamp Analysis of Anesthetic Interactions with Recombinant SK2 Subtype Neuronal Calcium-Activated Potassium Channels

Abstract: We describe differential effects of anesthetics on cloned small conductance calcium-activated potassium channels from brain that may play a role in generating the effects or side effects of anesthetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 29 publications
0
18
1
Order By: Relevance
“…These findings indicate that I KAS is important in ventricular arrhythmogenesis during hypokalemia. This may be relevant to drug safety, since a number of commonly used clinical drugs are known inhibitors of I KAS , such as anesthetic agents, 43 quinine, d -tubocurarine 44 and amiodarone. 45 It is possible that further investigations will discover the I KAS blocking action of other drugs used commonly in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that I KAS is important in ventricular arrhythmogenesis during hypokalemia. This may be relevant to drug safety, since a number of commonly used clinical drugs are known inhibitors of I KAS , such as anesthetic agents, 43 quinine, d -tubocurarine 44 and amiodarone. 45 It is possible that further investigations will discover the I KAS blocking action of other drugs used commonly in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to apamin, previous studies have shown that anesthetic agents, such as butanol, ethanol, ketamine, lidocaine, and methohexital block recombinant SK2 channel currents. 21 In addition, quinine, quinidine, d-tubocurarine, tetraethylammonium chloride and 4-aminopyridine are also I KAS blockers. 22 Preliminary investigation from our laboratory indicates that amiodarone is an effective I KAS blocker.…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol (≥10 mM) has been shown to inhibit SK channel (SK2 subtype)–mediated currents in a heterologous expression system (Dreixler et al ., 2000). Reduction in SK conductance may well lead to an enhancement of DA neuron pacemaker firing by suppressing AHPs.…”
Section: Acute Ethanol Action On Da Neuron Activitymentioning
confidence: 99%